THE ECONOMICS OF RECESSIONS: CAUSES AND RECOVERY - Munivenkatappa K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A recession represents a significant downturn in economic activity that affects multiple sectors of an economy, leading to falling output, rising unemployment, and reduced consumer and business confidence. Understanding the economics of recessions involves examining their causes, consequences, and the mechanisms through which economies recover. Recessions can be triggered by a variety of factors, including financial crises, asset bubbles, excessive inflation, restrictive monetary or fiscal policies, and external shocks such as global pandemics, geopolitical conflicts, or natural disasters. In many cases, these factors interact, amplifying economic instability and contributing to prolonged downturns. The impacts of recessions are far-reaching, often resulting in job losses, declining household incomes, business closures, reduced investment, and strained public finances. Vulnerable populations tend to suffer the most, with long-term unemployment and poverty levels increasing. Financial markets also face heightened volatility, as investor confidence deteriorates and access to credit tightens. Governments and central banks play a critical role in mitigating these effects through monetary and fiscal policy interventions. Measures such as interest rate reductions, quantitative easing, direct fiscal stimulus, and social safety nets are commonly employed to stabilize the economy and support recovery efforts. The path to recovery varies depending on the severity and underlying causes of the recession. Recoveries can be rapid or prolonged, with success often hinging on the effectiveness of policy responses and the resilience of economic structures. Structural reforms, improved financial regulations, and targeted support for affected industries and workers can enhance long-term economic stability and reduce vulnerability to future downturns. While recessions pose significant challenges, they also provide opportunities for economies to address structural weaknesses, foster innovation, and emerge more competitive and resilient. A comprehensive understanding of the causes and recovery processes is essential for policymakers, businesses, and individuals to navigate and overcome the complexities of economic downturns.